SOCIOLINGUISTIC FACTORS OF ENGLISH AND UZBEK PROVERBS AND SAYINGS - Munojat Umaraliyeva; Zarnigor Axmedova (TADQIQOTLAR.UZ, 2024)
Abstract: This article examines the sociolinguistic influences on English and Uzbek proverbs, analyzing their cultural origins, linguistic variations, and social implications. It explores how these linguistic expressions convey cultural wisdom, reflect societal norms, and adapt to changing contexts. Through this study, we gain insights into the dynamic interplay between language, culture, and society, highlighting the enduring relevance of proverbs in cross-cultural communication. Through a comprehensive analysis of sociolinguistic factors, this article contributes to a deeper understanding of language as a dynamic reflection of culture and society. It underscores the significance of proverbs and sayings in preserving cultural heritage, fostering intercultural communication, and enriching our appreciation of linguistic diversity.